Sports and pandemic: The debacle, its impact and aftermaths - Thomas, M. (Purakala, 2020)
Like an invisible enemy, covid-19 is destroying our sports world. Sports world is in such a state that even the Olympics cannot be held without eliminating the Covid -19 virus. Considering this situation I have prepared this research paper. There are fifteen questions of my own, which I have included in this survey. I have completed this survey with the help of Google forms. More than 180 international, national, state, inter university and university athletes aged 18 to 30 years are participated in the event. What I found from this survey is that athletes are very mentally exhausted, and the Covid-19 virus is losing the muscle strength and physical strength of athletes. They can't get physical training because they are in the rooms. They are also more likely to get into anti-depressants because of the psychological tension of what their future performances will be. So let the top authorities make every preparation to bring the sport back as soon as possible.